2010
DOI: 10.1094/pdis-94-8-1009
|View full text |Cite
|
Sign up to set email alerts
|

Aggressiveness of Phytophthora cactorum, P. citricola I, and P. plurivora from European Beech

Abstract: Phytophthora cactorum, P. citricola I, and P. plurivora cause bleeding cankers on mature European beech (Fagus sylvatica) trees in the northeastern United States. Inoculation experiments were conducted to compare the aggressiveness of the three Phytophthora spp. on stems, leaf disks, and roots of European beech and common lilac (Syringa vulgaris) seedlings. Isolates were obtained from bleeding cankers on European beech from five cities in New York (Albany, Ithaca, Oyster Bay, Plainview, and Rochester) and from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“…The inoculation experiment has revealed the pathogenicity of tested Phytophthora isolates, confirming the results from other similar studies (Weiland et al 2010;Jankowiak et al 2014). In our experiment, it was demonstrated that P. quercina can infect not only fine roots (Jung et al 1999;Jönsson et al 2003) but also tissues of Turkey oak stems.…”
Section: Discussionsupporting
confidence: 89%
“…The inoculation experiment has revealed the pathogenicity of tested Phytophthora isolates, confirming the results from other similar studies (Weiland et al 2010;Jankowiak et al 2014). In our experiment, it was demonstrated that P. quercina can infect not only fine roots (Jung et al 1999;Jönsson et al 2003) but also tissues of Turkey oak stems.…”
Section: Discussionsupporting
confidence: 89%
“…P. plurivora is distributed throughout Europe and North America and it is known to cause damage to dozens of forest and ornamental hosts including ericaceous plants Weiland et al 2010 (Pánek et al unpubl. ), from stem lesions of Alnus glutinosa, and from the root and collar rot of Acer pseudoplatanus (Černý et al unpubl.…”
Section: Phytophthora Plurivoramentioning
confidence: 99%
“…and Alnus spp. (Jung & Burgess 2009, Weiland et al 2010. Phytophthora plurivora has also been recently found to cause dieback and mortality of several deciduous tree species in Denmark, Norway and Poland (Talgø et al 2009, Thinggaard 2009, Orlikowski et al 2011.…”
Section: Phytophthora Plurivora and Ppinimentioning
confidence: 99%
“…Phytophthora plurivora has also been recently found to cause dieback and mortality of several deciduous tree species in Denmark, Norway and Poland (Talgø et al 2009, Thinggaard 2009, Orlikowski et al 2011. Phytophthora pini is widespread in the eastern US where it damages and kills the introduced species Syringa vulgaris and Fagus sylvatica L. (Jung et al 2005, Weiland et al 2010, Hong et al 2011. In contrast, in Europe it has only been found in nurseries, indicating a very recent introduction (Jung & Burgess 2009).…”
Section: Phytophthora Plurivora and Ppinimentioning
confidence: 99%
See 1 more Smart Citation